Perlindungan Konsumen terhadap Hak Memperoleh Informasi dalam Pembatalan Konser Secara Sepihak (Studi Kasus Konser K-pop We all are one) - Zidan Azayda Sabil; Indah Parmitasari (Fakultas Hukum Universitas Islam Indonesia, 2024)
The problem in this study is about how consumer protection in terms of obtaining the right to information in the case of unilateral cancellation of concerts and how the responsibility of promoters to ticket buyers due to unilaterally canceled concerts (K-pop concert